2021
DOI: 10.3389/fphys.2021.761760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menstrual Cycle or Hormonal Contraceptive Phase on Physiological Variables Monitored During Treadmill Testing

Abstract: Purpose: To examine the influence of menstrual cycle (MC) and hormonal contraceptive (HC) cycle phases on physiological variables monitored during incremental treadmill testing in physically active women (eumenorrheic, EUM = 16 and monophasic HC-users, CHC = 12).Methods: Four running tests to exhaustion were performed at bleeding, mid follicular (mid FOL)/active 1, ovulation/active 2, and mid luteal (mid LUT)/inactive. HC and MC phases were confirmed from serum hormones. Heart rate (HR), blood lactate (Bla), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The MC can be divided into three specific phases: the follicular phase (menses to ovulation), the ovulatory phase (at mid-cycle and lasts 24-48 h), and the luteal phase (from ovulation to next menses) (Hirschberg, 2022). Although the levels of estradiol and progesterone vary significantly during these phases, previous research investigating the effect of the MC on physical performance has shown varying results (Giacomoni et al, 2000;Oosthuyse, Bosch and Jackson, 2005;Bushman, Masterson and Nelsen, 2006;Shaharudin, Ghosh and Ismail, 2011;Vaiksaar et al, 2011;Julian et al, 2017;Barba-Moreno et al, 2019;McNulty et al, 2020;Taipale-Mikkonen et al, 2021). A recent meta-analysis concluded that muscle strength, as well as maximal and submaximal aerobic performance, are trivially reduced during the early follicular phase (during menses, low levels of estradiol, and progesterone), compared with all other MC phases (McNulty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The MC can be divided into three specific phases: the follicular phase (menses to ovulation), the ovulatory phase (at mid-cycle and lasts 24-48 h), and the luteal phase (from ovulation to next menses) (Hirschberg, 2022). Although the levels of estradiol and progesterone vary significantly during these phases, previous research investigating the effect of the MC on physical performance has shown varying results (Giacomoni et al, 2000;Oosthuyse, Bosch and Jackson, 2005;Bushman, Masterson and Nelsen, 2006;Shaharudin, Ghosh and Ismail, 2011;Vaiksaar et al, 2011;Julian et al, 2017;Barba-Moreno et al, 2019;McNulty et al, 2020;Taipale-Mikkonen et al, 2021). A recent meta-analysis concluded that muscle strength, as well as maximal and submaximal aerobic performance, are trivially reduced during the early follicular phase (during menses, low levels of estradiol, and progesterone), compared with all other MC phases (McNulty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, menses were not assessed in female participants. Nevertheless, it is questionable whether this would affect the findings of this study, as current evidence shows no systematic influence of the menstrual cycle on acute strength and endurance performance (Taipale-Mikkonen et al, 2021;Colenso-Semple et al, 2023). As the results of this study are cross-sectional, the question of compliance over time and the influence of training on strength determinants raises, which need to be investigated in further research.…”
Section: Limitationsmentioning
confidence: 76%
“…This study uses HRV and subjective recovery data as an average from two nights and days after the blood sample. Furthermore, in the CU group, data were analyzed from two nights of the active hormone weeks, where blood samples were not collected because endogenous sex hormone profile tends to remain stable during exogenous CU use (19,20). The participants in the NM and PU groups gave a fasted blood sample four times during the research period.…”
Section: Methodsmentioning
confidence: 99%
“…Maximal oxygen uptake (V̇O 2max ) was used to assess and describe the physical performance level of the participants. A treadmill test was performed using a standard incremental protocol 2–4 wk before the beginning of the study period similar to Taipale-Mikkonen et al (19). Briefly, for the first 3-min stage of the test, treadmill speed was 6–7 km·h −1 after which it was increased by 1 km·h −1 every third minute until volitional exhaustion.…”
Section: Methodsmentioning
confidence: 99%